2014
DOI: 10.4236/abc.2014.41006
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical screening, hepatoprotective and antioxidant effects of leaf extracts of <i>Zapoteca portoricensis</i>

Abstract: Fresh leaves of Zapoteca portoricensis are used in Eastern Nigeria for management/treatment of various disorders without any scientific basis. Hepatoprotective and antioxidant properties in albino rats, and phytochemical composition of distilled water and ethanol leaf extracts were studied. Fifty-five animals were placed in eleven groups (A-K) of five in each. Different doses (100, 200, 400 and 600 mg/kg body weight) of the extracts, 20 mg/kg body weight of vitamin C (standard antioxidant) and distilled water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…Study has shown that leaf extract of Z. portoricensis significantly increased malondialdehyde (MDA) levels and decrease superoxide dismutase (SOD) and catalase (CAT) activities in experimental rats. 23,24 This is an indication that the extract has antioxidative potential which is attributed to the presence of flavonoids in the extract, thus supports our present findings. The leaf extract of C. roseus (L. rosea) has been shown to reduce the serum cholesterol and total triglycerides levels in normal rats.…”
Section: Total Antioxidant Capacity (Tac)supporting
confidence: 92%
“…Study has shown that leaf extract of Z. portoricensis significantly increased malondialdehyde (MDA) levels and decrease superoxide dismutase (SOD) and catalase (CAT) activities in experimental rats. 23,24 This is an indication that the extract has antioxidative potential which is attributed to the presence of flavonoids in the extract, thus supports our present findings. The leaf extract of C. roseus (L. rosea) has been shown to reduce the serum cholesterol and total triglycerides levels in normal rats.…”
Section: Total Antioxidant Capacity (Tac)supporting
confidence: 92%
“…Epidemiologic studies recommend that coronary heart disease is opposed by dietary flavonoids (Wadood et al, 2013). Saponins detected in the fruit, is a known anti-nutritional factor, which reduces the uptake of certain nutrients including glucose and cholesterol at the gut through intralumenal physiochemical interactions (Shi et al, 2004;Agbafor et al, 2015). It has been reported to have hypocholesterolemic effects; hence it is useful in human diet in controlling cholesterol levels (James et al, 2010) and may aid in lessening the metabolic burden that would have been placed on the liver during metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…AST and ALT are enzymes that catalyze the transfer of α-amino groups from aspartate and alanine to the α-keto group of ketoglutaric acid to generate oxalacetic and pyruvic acids respectively when the liver is in toxic or stress condition, therefore serum concentrations of aminotransferases level increase. Several reports show that plants and phytochemicals attenuate the aminotransferases level [36]. The pretreatment of animals with the extracts P.kurroa resulted to a significant and dose dependent decrease in the levels of ALT and AST.…”
Section: Discussionmentioning
confidence: 96%